Multiple operant discrimination training to increase the precision of stimulus deltas following treatment of challenging behavior. (7th April 2021) - Lambert, Joseph M.; Lamers, Mallory E.; Copeland, Bailey A.; Banerjee, Ipshita
Abstract: Explicit instruction on how to maximize reinforcement in volatile reinforcement conditions could decrease the probability of persistent but ineffective requesting while also maintaining low rates of challenging behavior. We used a multiple probe design to demonstrate a functional relation between multiple‐operant discrimination training and manding for available reinforces from a child with autism spectrum disorder and complex communication needs who used a low‐tech augmentative and alternative communication system. Despite a history of severe challenging behavior, rates of challenging behavior remained low throughout this study.